Utilizing Technology in Social Work Education: Development of the Technology Effectiveness and Social Connectedness Scale. (3rd April 2021) - Jewell, Jennifer R.; Anthony, Becky; Murphy, April
ABSTRACT: The Council on Social Work Education understands the growing influence of technology on social work practice and education, including the need for students to develop the knowledge and skills to use modern technologies, including Twitter, both professionally and ethically. With the inclusion of technology in social work education, the efficacy of these methods must be assessed. This study aims to conduct the initial phase of scale development, an exploratory factor analysis. Using a purposive sample of over 200 BSW and MSW students in one university, this study presents results of the exploratory phase of the Technology Effectiveness and Social Connectedness Scale, which can be used to assess the effectiveness of incorporating Twitter into social work courses.